Oceanographic variability and change in two fjords in northern Norway - Bjørndalen, Elena (UiT Norges arktiske universitet, 2023)
Long-term hydrographic time series data from two fixed stations in the northern Norwegian fjords Malangen and Balsfjorden from the period 1980 - 2022 have been examined. The data have been supplemented with model results from the ocean model NorFjords160 over the period April 1st 2017 to December 31st 2022. To gain a deeper understanding of the oceanographic variability and change, the environmental drivers wind, precipitation and air temperature from the nearby weather stations Hekkingen fyr (Malangen) and Tromsø (Balsfjorden) and river runoff from the major rivers discharging in the fjords, Målselva (Malangen) and Nordkjoselva (Balsfjorden), have been examined for the same period. Additionally, for the years 2017 - 2022, particle tracking simulations have been used to investigate surface currents and the spread of particles from Målselva and Nordkjoselva. The findings reveal statistically significant, positive air temperature trends at both Hekkingen fyr and Tromsø (up to 2.2 °???? in autumn over the period 1980 - 2022). There is found seasonal variations in precipitation, however there are no discernible trends in river runoff at either locations. For the hydrographic conditions, the findings reveal statistically significant, positive temperature trends for both the surface layer (0.03 - 0.06 °C yr−1 in Malangen and 0.04 - 0.07 °C yr−1 in Balsfjorden) and deep layers (0.03 - 0.04 °C yr−1 in Malangen and 0.01 - 0.04 °C yr−1 in Balsfjorden) throughout all four seasons, in both fjords. There are no statistically significant trends regarding deep layer salinity in Malangen, whereas in Balsfjorden there is a statistically significant, negative trend in the spring and summer surface layers, as well as the summer deep layer. I hypothesize that the changes in temperature are linked to warming of the coastal water masses observed over the same period (Albretsen et al.,2011a; IMR, 2023), and the observed increase in air temperature. During the study period the surface CW has gotten fresher, while the deep CW has gotten ...